PERGURUAN THAWALIB PADANG PANJANG IN THE PERSPECTIVE OF EDUCATIONAL HISTORY 1912 - 1926 - Harmonedi Harmonedi (Balai Pelestarian Nilai Budaya Sumatera Barat, 2020)
Perguruan Thawalib Padang Panjang has contributed greatly to the nation. The history of its establishment cannot be separated from Surau Jembatan Besi. To uncover this problem the authors conducted research under the title